2016
DOI: 10.1111/1755-0998.12635
|View full text |Cite
|
Sign up to set email alerts
|

Breaking RAD: an evaluation of the utility of restriction site‐associated DNA sequencing for genome scans of adaptation

Abstract: Understanding how and why populations evolve is of fundamental importance to molecular ecology. Restriction site-associated DNA sequencing (RADseq), a popular reduced representation method, has ushered in a new era of genome-scale research for assessing population structure, hybridization, demographic history, phylogeography and migration. RADseq has also been widely used to conduct genome scans to detect loci involved in adaptive divergence among natural populations. Here, we examine the capacity of those RAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
288
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 346 publications
(296 citation statements)
references
References 92 publications
5
288
1
2
Order By: Relevance
“…Recently, there has been debate regarding whether reduced representation genome sequencing approaches can identify SNPs at high enough densities to perform the kinds of association studies presented here [61]. For example, a reduced representation genome scan of Vermivora warblers failed to detect highly divergent genomic regions, which were only discovered after whole-genome sequencing [18].…”
Section: (C) Heterogeneous Differentiation and Warbler Speciationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, there has been debate regarding whether reduced representation genome sequencing approaches can identify SNPs at high enough densities to perform the kinds of association studies presented here [61]. For example, a reduced representation genome scan of Vermivora warblers failed to detect highly divergent genomic regions, which were only discovered after whole-genome sequencing [18].…”
Section: (C) Heterogeneous Differentiation and Warbler Speciationmentioning
confidence: 99%
“…Using simulations, Kardos et al [62] showed that tens of thousands of SNP markers may not be adequate to detect genotype-phenotype associations in natural populations, and recommended wholegenome sequencing of extreme phenotypes. Lowry et al [61] argued that most reduced-representation sequencing studies genotype far too few SNPs to find significant associations, given the extent of linkage disequilibrium. However, when linkage disequilibrium is high, such as in hybrid zones (e.g.…”
Section: (C) Heterogeneous Differentiation and Warbler Speciationmentioning
confidence: 99%
“…While providing high resolution for population genetic studies, RAD‐based approaches survey only a small proportion of the genome (Lowry et al., 2017). We are therefore likely to have missed the vast majority of loci that may be under selection between the global and Bocas‐specific populations.…”
Section: Discussionmentioning
confidence: 99%
“…Association (population-based) or QTL (pedigree-based) mapping could then be used to identify genes that are related to local adaptation, but this is contingent on identification of genetically differentiated populations. Restriction site associated DNA sequencing (RADseq) is an excellent tool for population genetic studies but may provide insufficient genomic coverage to detect regions under local selection (Lowry et al 2017). In the absence of full genomic sequences, transcriptomic or exome capture techniques provide a relatively high coverage of genic regions (Lowry et al 2017).…”
Section: Local Adaptationmentioning
confidence: 99%
“…Restriction site associated DNA sequencing (RADseq) is an excellent tool for population genetic studies but may provide insufficient genomic coverage to detect regions under local selection (Lowry et al 2017). In the absence of full genomic sequences, transcriptomic or exome capture techniques provide a relatively high coverage of genic regions (Lowry et al 2017). While methods that provide a sampling of loci across the entire genome, such as RADseq, alone are insufficient tests of local adaptation, they are important in identifying patterns potentially associated with adaptation and provide a wealth of valuable information on population structure and allele frequencies.…”
Section: Local Adaptationmentioning
confidence: 99%